P PENGEMBANGAN GAME EDUKASI “PETUALANGAN ALJA” UNTUK MELATIH CONCEPTUAL UNDERSTANDING DAN PROCEDURAL FLUENCY SISWA SMP MATERI ALJABAR: pengembangan game edukasi mateei aljabar - Wicaksono, Gesit (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2021)
Games are one of the entertainments that are often and in demand by many children, especially those that can be used in electronic media. The educational game media developed in this research is